Improvement of enzymatic bioxylitol production from sawdust hemicellulose: optimization of parameters - Rafiqul, Islam S. M.; Mimi Sakinah, Abdul Munaim; Zularisam, Abdul Wahid (Taylor and Francis Ltd, 2021)
Enzymatic production of bioxylitol from lignocellulosic biomass (LCB) provides a promising alternative to both chemical and fermentative routes. This study aimed to assess the impacts of catalytic variables on bioxylitol production from wood sawdust using xylose reductase (XR) enzyme and to optimize the bioprocess. Enzyme-based xylitol production was carried out in batch cultivation under various experimental conditions to obtain maximum xylitol yield and productivity. The response surface methodology (RSM) was followed to fine-tune the most significant variables such as reaction time, temperature, and pH, which influence the synthesis of bioxylitol from sawdust hydrolysate and to optimize them. The optimum time, temperature, and pH became were 12.25 h, 35 degrees C, and 6.5, respectively, with initial xylose 18.8 g/L, NADPH 2.83 g/L, XR 0.027 U/mg, and agitation 100 rpm. The maximum xylitol production was attained at 16.28 g/L with a yield and productivity of 86.6% (w/w) and 1.33 g/L center dot h, respectively. Optimization of catalytic parameters using sequential strategies resulted in 1.55-fold improvement in overall xylitol production. This study explores a novel strategy for using sawdust hemicellulose in bioxylitol production by enzyme technology.